The critical nature of non-verbal signals in negotiation - Adair, Wendi (Henry Stewart Talks, 2013)
Negotiation, Nonverbal communication, Power, Building relationships, Mimicry, Emotion expression, Claiming value, Creating value, Engagement, Culture